Vaccination after spleen embolization: A practice management guideline from the Eastern Association for the Surgery of Trauma. Issue 11 (November 2022) - Freeman, Jennifer J.; Yorkgitis, Brian K.; Haines, Krista; Koganti, Deepika; Patel, Nimitt; Maine, Rebecca; Chiu, William; Tran, Thai L.; Como, John J.; Kasotakis, George
Highlights: Embolization patients had fewer infectious complications and greater preservation of splenic immune function when compared to splenectomy patients. Splenectomy patients had a significantly poorer response to vaccination when compared to embolized patients. Several studies found no difference between embolization and normal controls. We conditionally recommend against routine post-splenectomy vaccinations in adult trauma patients who have undergone angioembolization for splenic injury. Abstract: Background: Angioembolization is an important adjunct in the non-operative management of adult trauma patients with splenic injury. Multiple studies have shown that angioembolization may increase the non-operative splenic salvage rate for patients with high-grade splenic injuries. We performed a systematic review and developed evidence-based recommendations regarding the need for post-splenectomy vaccinations after splenic embolization in trauma patients. Methods: A systematic review and meta-analysis of currently available evidence were performed utilizing the Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology. Results: Nine studies were identified and analyzed. A total of 240 embolization patients were compared to 443 control patients who neither underwent splenectomy nor were embolized. There was no statistical difference between the splenic immune function of embolized and control patients. In addition, a total of 3974 splenectomy patients was compared with 686 embolization patients. Embolization patients had fewer infectious complications and a greater degree of preserved splenic immune function. Conclusion: In adult trauma patients who have undergone splenic angioembolization, we conditionally recommend against routine post-splenectomy vaccinations. Study type : systematic review/meta-analysis Level of evidence : level III